Ablasi Radiofrekuensi pada Kepak Atrium Tipikal Setelah Pemasangan Amplatzer Septal Occluder : Suatu Laporan Kasus - Siska Suridanda Danny; Yoga Yuniadi; Amir Aziz Alkatiri; Faris Basalamah; Muhammad Munawar (Jurnal Kardiologi Indonesia, 2008)
We report a case of a 48-year old female with secundum atrial septal defect (ASD), already undergone device closure with an Amplatzar Septal Occluder (ASO). The patient subsequently underwent radiofrequency catheter ablation for typical atrial flutter, three months after ASD closure with good results. During follow up the patient remained in sinus rhythm and the complaints of dyspnoe and palpitation subsided.